2018
DOI: 10.20849/ijsn.v3i3.466
|View full text |Cite
|
Sign up to set email alerts
|

Appearance of Nurses and Perceived Professionalism

Abstract: Background: After completing a literature review on the topic of appearance and professionalism a knowledge gap was identified, relating to how individuals perceive professionalism based on appearance. First impressions are how patients form opinions of their nurses. Professionalism is influenced by many variables, such as hair, make-up, uniform, behavior, and image. Purpose: The purpose of this study was to explore perceptions of a nurse’s appearance and projected professionalism. Method: A total of 120 stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 8 publications
(27 reference statements)
0
17
0
2
Order By: Relevance
“…Appendix B lists the interview questions. It is worth noting that the interview questions were developed based on the recommendations and guidelines of SCCT [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ], recent studies [ 6 , 7 ], and the objectives of the study.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Appendix B lists the interview questions. It is worth noting that the interview questions were developed based on the recommendations and guidelines of SCCT [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ], recent studies [ 6 , 7 ], and the objectives of the study.…”
Section: Methodsmentioning
confidence: 99%
“…In general, nursing occupations are stable and come with a higher social status, but are also characterised by work and responsibility overloads, usually causing their practitioners to be tired, and are low-paying in order to broaden opportunities across occupational disciplines for those entering the workforce [ 8 ]. Although work–life responsibilities are not balanced due to human resource shortages, it is important to increase the overall enrolment and experience of nursing students and in-service nursing professionals in order to ensure adequate workforce management [ 9 ]. A previous study [ 2 , 10 ] indicated that a large number of mid-level and senior-level nursing professionals decided to leave the profession due to poor administrative management, overloaded working responsibilities, insufficient salaries, and regular overtime.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the sharing about the model of their children and family members, a previous study indicated that many nurses tended to establish a positive image and model [ 60 , 61 , 62 , 63 ] as learning tools [ 78 ]. Indeed, only a few of this study’s participants were single people without children.…”
Section: Discussionmentioning
confidence: 99%